2023
DOI: 10.1093/hr/uhad061
|View full text |Cite
|
Sign up to set email alerts
|

The complete reference genome for grapevine (Vitis viniferaL.) genetics and breeding

Abstract: Grapevine is one of the most economically important crops worldwide. However, the previous versions of the grapevine reference genome consisted of thousands of fragments with missing centromeres and telomeres, which limited the accessibility of the repetitive sequences, the centromeric and telomeric regions, and the inheritance of important agronomic traits in these regions. Here, we assembled a telomere-to-telomere (T2T) gap-free reference genome for the pinot noir cultivar (PN40024) using the PacBio HiFi lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 82 publications
4
57
0
Order By: Relevance
“…4a, b). Our results showed that the occurrence of two polyploidization events in the C. crapnelliana genome, including the ancient WGT (γ) event that occurred in grape and eudicots 60,61 , the other WGD (β) event shared with A. chinensis and other Theaceae species 11,54,84 (Fig. 4a, b).…”
Section: Genome Synteny Analysis and Detection Of Whole-genome Duplic...mentioning
confidence: 73%
See 1 more Smart Citation
“…4a, b). Our results showed that the occurrence of two polyploidization events in the C. crapnelliana genome, including the ancient WGT (γ) event that occurred in grape and eudicots 60,61 , the other WGD (β) event shared with A. chinensis and other Theaceae species 11,54,84 (Fig. 4a, b).…”
Section: Genome Synteny Analysis and Detection Of Whole-genome Duplic...mentioning
confidence: 73%
“…The protein-coding genes of nine representative species were selected for gene family analysis using OrthoFinder v2.5.4 73 oleifera 26 (CON), Olea europaea 57,74 (OEU), Vitis vinifera 60,61 (VVI), and C. crapnelliana (CCRA). A total of 107 single-copy orthologues were obtained, and they were aligned using MAFFT v7.505 75 , and then ProTest v3.4.2 76 was used to find the best model of amino acid replacement in the single-copy alignments.…”
Section: Comparative Genomic Analysismentioning
confidence: 99%
“…A. chinensis (Han et al, 2023), http://182.92.183.62/; C. limon (Bao et al, 2023), https://ngdc.cncb.ac.cn/search/?dbId=gwh&q=GWHCBFQ00000000.1; E. rufpilus (Wang et al, 2023), http://sugarcane.zhangjisenlab.cn/SugarcaneDB/#/downloads; O. sativa (Song et al, 2021), http://rice.hzau.edu.cn/cgi-bin/rice_rs3/download_ext; V. vinifera (Shi et al, 2023), https://zenodo.org/record/7751391#.ZBgVmcJBy3A; Z. mays (Chen et al, 2023), https://www.ncbi.nlm.nih.gov/bioproject/?term=PRJNA751841.…”
Section: Dataset Download and Usage Of Toolsmentioning
confidence: 99%
“…The wet-experiment-based method utilizes centromere-specific proteins (CenH3 in plants) to perform Chromatin Immunoprecipitation Sequencing (ChIP-seq) and maps centromeric reads to the assembly for identification, which is costly and time-consuming (Liu et al, 2023;Marques et al, 2015). The bioinformatics method detects all tandem repeat monomers (TRs) in the whole genome first, and performs the identification by assuming the centromeric TRs are the most abundant among all TRs of a genome (Shi et al, 2023). For example, quarTeT can be used for identifying centromeric repeats (Lin et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…PN40024) obtained after several rounds of selfing of the cultivar Helfensteiner, the result of Pinot noir and Schiava grossa outcross 1,2 . The PN40024 reference genome has been a key tool for the study of grapevine molecular biology and genetics and both the reference assembly and annotation have been continuously improved [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%